A DNA pooling based system to detect Escherichia coli virulence factors in fecal and wastewater samples - Cortés Bratti, Ximena (2012)
The availability of a useful tool for simple and timely detection of the most important virulent varieties of Escherichia coli is indispensable. To this end, bacterial DNA pools which had previously been categorized were obtained from isolated colonies as well as selected in terms of utilized phenotype; the pools were assessed by two PCR Multiplex for the detection of virulent E. coli eaeA, bfpA, stx1, stx2, ipaH, ST, LT, and aatA genes, with the 16S gene used as DNA control. The system was validated with 66 fecal samples and 44 wastewater samples. At least one positive isolate was detected by a virulent gene among the 20 that were screened. The analysis of fecal samples from children younger than 6 years of age detected frequencies of 25% LT positive strains, 8.3% eae, 8.3% bfpA, 16.7% ipaH, as well as 12.5 % aatA and ST. On the other hand, wastewater samples revealed frequencies of 25.7% eaeA positive, 30.3% stx1, 15.1% LT and 19.7% aatA. This study is an initial step toward carrying out epidemiological field research that will reveal the presence of these bacterial varieties.